Global food crises: Monitoring and assessing impact to inform policy responses - Benson, Todd; Minot, Nicholas; Pender, John L.; Robles, Miguel; von Braun, Joachim (International Food Policy Research Institute, 2008)
Strong upward trends and increased variability in global food prices during the past two years have led to concern that hunger and poverty will increase across the world. At the same time, rising food prices provide an incentive and opportunity for many developing countries to strengthen the contribution their farmers make to national economic growth and poverty reduction. Policymakers and opinion leaders in developing countries, however, often lack sufficient information to gauge the likely effects of global food crises on their country and to identify, design, and implement policy actions that can best avoid risks and take advantage of opportunities. The deficiencies in information and analysis can lead to overand underreactions, resulting in policy and market failures. Experiences across countries in 2007 and 2008 show ample evidence of such outcomes. Although the food crisis information currently available is alarming and sufficient to initiate largescale action, the information base must be improved to make that action more effective.